A circular monopole patch antenna loaded with inverted L-shaped stub for GPS application - Sowmya G. A.; Akshtha Kamath; Anala Keshava; Om Prakash Kumar; Shweta Vincent; Tanweer Ali (Institute of Advanced Engineering and Science, 2020)
This article introduces a planar monopole patch antenna for global positioning system (GPS) application. Our design has a circular patch with a stub of inverted L-shape which is used as the radiating portion and partial ground. Our proposed design of the stub allows the antenna to operate at a frequency of 1.5 GHz. The circular monopole is fed by an offset feeding to have an impedance match of 50 ohms. The compact antenna has been designed and simulated on RT Duroid 6006 material with relative permittivity ( ) of 6.15 and 0.0019 as the loss tangent. Our antenna has a dimension of 65 × 55 × 2.54 mm3 . A gain of 1.23 dB is observed at the resonant frequency of 1.5 GHz and the antenna exhibits dipole like radiation pattern both in E and H-plane. The antenna has better impedance matching, good gain and steady characteristics of radiation pattern across the operating bandwidth. High frequency structure simulator (HFSS) v.13.0 is used to carry out all the simulations.